Algorithmic Inventory of Cultural Artefacts (Case Study: Rumoh Aceh of Indonesia) - ., Atthaillah; Wijayanti, Suhartina; Iqbal, Muhammad; Azmah Fithri, Cut (International Journal of Engineering and Technology, 2019)
The existence of rumoh Aceh as a cultural artifact had faced its hardest time. Aspects such as social, economic and environment were considered responsible for the problem. Firstly, within social aspect rumoh Aceh considered inappropriate to accommodate a more modern way of life of the Acehnese. Also, the scarcely available of Acehneseâ€™s carpenters who were able to construct a traditional house contribute to an even worse situation. Secondly, in term of economic aspect, budget required to build a traditional house was becoming more expensive. Lastly, nonexistent of environmentally friendly wood production was further considered to responsible for an extinct possibility of rumoh Aceh. Some efforts had been conducted to preserve the artifact in a conventional method using two dimensional working drawing system. The conventional method had not ready for the future technology, and difficult to understand for non-technical peoples. This research improved a conventional inventory model into a more sophisticated data based system utilizing algorithmic method. Further, this study integrated visual scripting of Grasshopper for the algorithmic inventory system. The algorithms was offered to store a real three dimensional data and prepare to be ready for a future production technology such as digital fabrication. As a result, this technological innovation became an alternative solution to preserve the cultural artifact of Rumoh Aceh.Â